Arabidopsis ATG8-INTERACTING PROTEIN1 Is Involved in Autophagy-Dependent Vesicular Trafficking of Plastid Proteins to the Vacuole . Issue 10 (3rd October 2014) - Michaeli, Simon; Honig, Arik; Levanony, Hanna; Peled-Zehavi, Hadas; Galili, Gad
Abstract : A previously unrecognized plastid-to-vacuole protein trafficking pathway that is stress induced and autophagy dependent appears to involve ATI1 interaction with plastid proteins and ATG8 of the core autophagy machinery. Abstract: Selective autophagy has been extensively studied in various organisms, but knowledge regarding its functions in plants, particularly in organelle turnover, is limited. We have recently discovered ATG8-INTERACTING PROTEIN1 (ATI1) from Arabidopsis thaliana and showed that following carbon starvation it is localized on endoplasmic reticulum (ER )-associated bodies that are subsequently transported to the vacuole. Here, we show that following carbon starvation ATI1 is also located on bodies associating with plastids, which are distinct from the ER ATI bodies and are detected mainly in senescing cells that exhibit plastid degradation. Additionally, these plastid-localized bodies contain a stroma protein marker as cargo and were observed budding and detaching from plastids. ATI1 interacts with plastid-localized proteins and was further shown to be required for the turnover of one of them, as a representative. ATI1 on the plastid bodies also interacts with ATG8f, which apparently leads to the targeting of the plastid bodies to the vacuole by a process that requires functional autophagy. Finally, we show that ATI1 is involved in Arabidopsis salt stress tolerance. Taken together, our results implicate ATI1 in autophagic plastid-to-vacuole trafficking through its ability to interact with both plastid proteins and ATG8 of the core autophagy machinery.